FREQUENCY OF PIPERACILLIN/TAZOBACTAM RESISTANCE IN SPONTANEOUS BACTERIAL PERITONITIS PATIENTS - IBRAHIM , M; ASLAM, M; RAHMAN, MU; RAHMAN, SU; ZAMAN, SU; KHALIL, MUK (Biological and Clinical Sciences Research Journal, 2024)
Spontaneous bacterial peritonitis (SBP) is a serious infection in patients with chronic liver disease, requiring prompt antibiotic therapy. Due to growing resistance to first-line antibiotics like ceftriaxone, piperacillin/tazobactam is often used as a second-line treatment. However, emerging resistance to piperacillin/tazobactam poses a significant clinical challenge. Identifying local resistance patterns is crucial for optimizing treatment, particularly in resource-limited settings like Peshawar, Pakistan. Objective: To determine the frequency of piperacillin/tazobactam resistance among patients with spontaneous bacterial peritonitis at a tertiary care hospital in Peshawar, Pakistan. Methods: This cross-sectional study was conducted over five months at Lady Reading Hospital, Peshawar from 18th April to 18th September. A total of 169 patients aged 16 to 75 years with SBP secondary to chronic liver disease were included using non-probability consecutive sampling. Demographic and clinical data were collected, and ascitic fluid samples were cultured to assess resistance to piperacillin/tazobactam. Data were analyzed using descriptive statistics and chi-square tests to examine associations. A p-value < 0.05 was considered statistically significant. Results: Piperacillin/tazobactam resistance was found in 9.5% (16/169) of SBP patients. Resistance was observed in 8.0% (7/88) of Escherichia coli isolates and 11.1% (9/81) of other bacterial isolates (p = 0.04). Resistance rates were slightly higher in the 46–75 age group (11.0%, 11/100) compared to the 16–45 age group (7.3%, 5/69). Male patients had a resistance rate of 10.2% (11/108), while female patients showed 8.2% (5/61). Conclusion: This study highlights significant resistance to piperacillin/tazobactam among SBP patients in Peshawar, particularly in non-E. coli bacteria. These findings underline the need for personalized antibiotic regimens and ongoing surveillance to address growing antimicrobial resistance in chronic liver disease patients.